Reverse engineering of micro light aircraft systems and design - Wan Hassan, Wan Azizurrahman (2014)
Humans tends to get bored when doing a repetitive task over and over again. Whenever human get bored doing something, their concentration level on doing the task will go down and the end result of the task will not be up to the standard. A robot that can imitate human movement could be introduce in order to reduce human error in doing a repetitive task. But, to design a robot that could impersonate human movement is not that easy. Designer need to try and re-try their design before implement it in a real robot. In order to simplify the design and development of a robot, this thesis present the modelling and control of articulated robot arm. The robot arm is modelled using a CAD model that was design in SolidWorks. The robot arm movement is then simulated using the CAD model in Simulink before implementing in the real model. The robot arm is controlled by Arduino Uno that interact directly to the Simulink. The robot arm movement follows the CAD model movement which is being simulated in the Simulink. Two type of analysis has been done for this project that is an open and closed loop control test and also durability and reliability test. This prototype of the robot arm showed that the operational was successful with the initial open loop error that range from 11.48% till 15.56% to be reduced down to a maximum eror of 1.64%, the robot arm able to lift loads that are not more than 160 gram and produce error not more than 20%. Overall, this new approach of designing and control of a robot is a success.